Muzeum Libeskina w Berlinie jako wieża, która runęła - Kamczycki, Artur (Studia Europaea Gnesnensia, 2015)
In the article the author will attempt to interpret the architectural structure of the Jewish Museum in Berlin, designed in 1989 by Daniel Libeskind. The context of deliberations presented here will rely on a broadly understood idea of tower, an entity identical with the Judaic as well as Christian vision of the Heavenly Jerusalem. However, the key to the metaphor is the assumption that the structure symbolizes a toppled tower, which in its turn is a meaningful analogy to the concepts derived from the issues of the Holocaust.